1999
DOI: 10.1137/s0036142997328111
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis for the Numerical Evaluation of the Diagonal Forms of the Scalar Spherical Addition Theorem

Abstract: The numerical solution of wave scattering from large objects or from a large cluster of scatterers requires excessive computational resources and it becomes necessary to use approximatebut fast-methods such as the fast multipole method; however, since these methods are only approximate, it is important to have an estimate for the error introduced in such calculations. An analysis of the error for the fast multipole method is presented and estimates for truncation and numerical integration errors are obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 25 publications
1
84
0
Order By: Relevance
“…A particularly crucial point of the implementation is the interpolation and anterpolation steps. We here presented a variant of the scheme proposed by Chew and Lu in [41]. Its complexity is O(K ), if K is the number of samples in S 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly crucial point of the implementation is the interpolation and anterpolation steps. We here presented a variant of the scheme proposed by Chew and Lu in [41]. Its complexity is O(K ), if K is the number of samples in S 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We will discuss here the scheme due to Alpert and Jakob-Chien [5] and the one due to Song, Lu, and Chew [40,41,53].…”
Section: Interpolation Algorithmsmentioning
confidence: 99%
“…Greengard and Rokhlin were the first authors to provide empirical laws for the truncation integer L that achieves a given precision, at least when v is not too large. Those formulas have been fixed and improved by Chew and Song [17], (see also Chew [8]), but with no precise analytical error estimates. On the other hand, Rahola [21] then Darve [11], gave precise results, i.e.…”
Section: Motivationmentioning
confidence: 99%
“…Rahola [21] showed that the series was bounded by a geometrical series, Darve [11] analyzed more precisely the absolute error, and Koc et al [17] gave some elements of analysis, and mentioned the formula…”
Section: The Gegenbauer Seriesmentioning
confidence: 99%
See 1 more Smart Citation